Draft Third Five Year Plan October 1960 Shilong - Planning Commission (Planning Commission, 1960)
In keeping with the objectives of the All-India Plan, we have given agriculture an important place both from the point of financial and physical targets, The largest single item of expenditure is, however, proposed under engineering with major emphasis being on the development of roads and communications right up to the International Border; as apart from considerations of defence our experience has shown that the absence of proper communications in the interior of NEFA is still the major retarding factor in all our development activities.
North-East Frontier Agency
North-East Frontier Agency